A study to compare perception of weight training as an equally useful and proper exercise modality as compared to walking in obese men - Rajadnya, Vikram A.; Tilak, Abhijeet Vijay; Rajadnya, Chaitra V.; Manjare, Rahul Maruti; Rane, Bhalchandra T.; Patil, Suhas H. (International Journal Of Community Medicine And Public Health, 2017)
Background:This study was intended to evaluate perception of the young adult obese men towards weight training as a proper and useful modality as compared to walking. Methods:The study was a questionnaire based and conducted in a weight management clinic in Maharashtra state, India. Obese men between 18-40 years of age during their first visit were studied for their perception about weight training. Results:There was no significant difference between the scores with walking and weight training. Conclusions:Our results clearly indicate that weight training is perceived to be an equally proper and useful modality of exercise as compared with walking amongst obese men.